Improving the removal of fine particles from coal combustion in the effect of turbulent agglomeration enhanced by chemical spray. (15th December 2018) - Sun, Zongkang; Yang, Linjun; Shen, Ao; Hu, Bin; Wang, Xiaobei; Wu, Hao
Highlights: The chemical spray was added to enhance the effect of turbulent agglomeration. The chemical-turbulent agglomeration had better effects on fine particle agglomeration. High removal efficiency was obtained by chemical-turbulent agglomeration. The adhesion force between fine particles was strengthened after chemical spray. The value of turbulent agglomeration kernel increased after chemical spray. Abstract: Turbulent agglomeration is a simple and economical method to improve the agglomeration of fine particles from coal combustion, which is beneficial to the particle removal efficiency of conventional equipment. However, the agglomeration efficiency for fine particles is low by single turbulent agglomeration because of the weak adhesion forces between particles, which leads to plenty of ineffective collisions. In this study, a novel technique was presented to improve the effect of fine particles agglomeration in turbulent agglomeration by adding chemical spray. The influence of single turbulent agglomeration and chemical-turbulent agglomeration on fine particle concentrations, particle size distributions, ESP performance, particle removal efficiencies in different stages and total dust concentrations after ESP were investigated respectively. The results showed the chemical-turbulent agglomeration had better effects on the agglomeration and removal of fine particles than single turbulent agglomeration. After chemical-turbulent agglomeration, the PM10 number concentration decreased about 34.1% than single turbulent agglomeration, and particle number concentration dropped at each stage under 10 µm, especially at 0.1 µm. Meanwhile, the application of chemical-turbulent agglomeration led to the number removal efficiency of PM10 increasing from 82.6% to 89.9%, the mass removal efficiency increasing from 84.5% to 91.8%, and the total dust concentrations after ESP reducing about 638 mg·m −3 than single turbulent agglomeration, respectively. Furthermore, the enhancement mechanism of chemical-turbulent agglomeration was explored by analyzing adhesion forces between particles and calculating the turbulent agglomeration kernel. In this study, the capillary and solid-bridge forces between particles and the increasing value of KTS after chemical spray were considered as the main reasons for better effects of chemical-turbulent agglomeration.